Soil-pile interaction effects in wharf structures under lateral loads - Doran, Bilge; Seckin, Aytug (TECHNO-PRESS, 2014)
Wharfs are essential to shipping and support very large gravity loads on both a short-term and long-term basis which cause quite large seismic internal forces. Therefore, these structures are vulnerable to seismic activities. As they are supported on vertical and/or batter piles, soil-pile interaction effects under earthquake events have a great importance in seismic resistance which is not yet fully understood. Seismic design codes have become more stringent and suggest the use of new design methods, such as Performance Based Design principles. According to Turkish Code for Coastal and Port Structures (TCCS 2008), the interaction between soil and pile should somehow be considered in the nonlinear analysis in an accurate manner. This study aims to explore the lateral load carrying capacity of recently designed wharf structures considering soil-pile interaction effects for different soil conditions. For this purpose, nonlinear structure analysis according to TCCS (2008) has been performed comparing simplified and detailed modeling results.
Keywords: pile-wharf structures; nonlinear soil springs; equivalent length; pushover analysis; Engineering